The Existence and Attractivity of Solutions of an Urysohn Integral Equation on an Unbounded Interval - Mohamed Abdalla Darwish; Józef Banaś; Ebraheem O. Alzahrani (Abstract and Applied Analysis)
We prove a result on the existence and uniform attractivity of solutions of an Urysohn integral equation. Our considerations are conducted in the Banach space consisting of real functions which are bounded and continuous on the nonnegative real half axis. The main tool used in investigations is the technique associated with the measures of noncompactness and a fixed point theorem of Darbo type. An example showing the utility of the obtained results is also included.